Syngas Production Through H2O/CO2 Thermochemical Splitting Over Doped Ceria-Zirconia Materials - Luciani, Giuseppina; Landi, Gianluca; Di Benedetto, Almerinda (Frontiers in Energy Research, 2020)
Ceria-zirconia (CeZr) catalysts co-doped with K+ and either Cu2+ or Fe3+ cations were studied in the co-splitting of water and carbon dioxide. Both materials are able to separately split CO2 and H2O into CO and H2 respectively. Co-splitting tests were carried out. On K-Cu-CeZr catalyst water reacts faster and negligible CO production is detected. In the case of K-Fe-CeZr catalyst, two peaks are found: at low temperature, only H2 is produced while at high temperature, CO is preferentially produced. A kinetic model was developed to get insights into the reason for the observed selectivity toward H2 at low temperature and CO at higher temperature. Different reaction orders of CO2 and H2O reactions with respect to the site fraction were found highlighting that H2 production requires a larger number of adjacent reduced sites than CO production. From the model, three regimes were identified: Regime I- H2O driven regime @T≤650 °C; Regime II- mixed regime @ 560 < T < 700 °C and Regime III: CO2 driven regime @ T > 700 °C. These results may drive the choose of the appropriate conditions for getting the desired H2/CO selectivity, depending on the type of feed.